2018
DOI: 10.3168/jds.2018-14579
|View full text |Cite
|
Sign up to set email alerts
|

Typeability of MALDI-TOF assay for identification of non-aureus staphylococci associated with bovine intramammary infections and teat apex colonization

Abstract: Matrix-assisted laser desorption/ionization time of flight (MALDI-TOF), a culture-dependent assay, has recently been implemented for routine identification of non-aureus staphylococci (NAS) species from milk, but the assay has never been investigated for NAS from nonmilk or environmental samples. The objective of this study was to evaluate the typeability of the MALDI-TOF assay for the identification and differentiation of bovine-associated NAS species on aseptically collected quarter milk and teat skin sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 52 publications
(85 reference statements)
2
27
0
Order By: Relevance
“…Mixed staphylococci species were found significantly more often in teat canal swabs samples (19.1%) than in milk samples (3.6%), except in herd C. The high presence of flies in this herd, as observed during the regular herd visits and the longitudinal study preceding the current study (23), might influence the bacteria population on teats and in teat canals since they may transmit bacteria causing IMI (43, 44). The same definition for mixed staphylococcal species was used in our above-mentioned previous study and also by Mahmmod et al (24). In order to avoid preclusion of potentially relevant information, considering that the teat canal—similar to teat apices—harbors many different NAS species (8, 1518) and taking into account the duality of its role—as a barrier against IMI on one side and potential reservoir for NAS species causing IMI on the other—the decision to include culture results with up to three Staphylococcus species was made.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Mixed staphylococci species were found significantly more often in teat canal swabs samples (19.1%) than in milk samples (3.6%), except in herd C. The high presence of flies in this herd, as observed during the regular herd visits and the longitudinal study preceding the current study (23), might influence the bacteria population on teats and in teat canals since they may transmit bacteria causing IMI (43, 44). The same definition for mixed staphylococcal species was used in our above-mentioned previous study and also by Mahmmod et al (24). In order to avoid preclusion of potentially relevant information, considering that the teat canal—similar to teat apices—harbors many different NAS species (8, 1518) and taking into account the duality of its role—as a barrier against IMI on one side and potential reservoir for NAS species causing IMI on the other—the decision to include culture results with up to three Staphylococcus species was made.…”
Section: Discussionmentioning
confidence: 96%
“…Teat canal swabs and milk samples with more than three different NAS species on the selective agar plates were considered as mixed staphylococcal species (23, 24). Incidentally growing non-staphylococci species were not considered for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, nowadays, veterinary diagnostic laboratories favour mass spectrometry (for instance, matrix‐assisted laser desorption‐ionization–time of flight mass spectrometry or MALDI‐TOF MS ® ) for the identification of bacterial species. The MALDI‐TOF MS databases for the different bacterial genera and families in veterinary medicine are indeed progressively validated like recently the database of staphylococcal species associated with bovine mastitis (Cameron et al, , ; Mahmmod et al, ; Nonnemann et al ). However, a delay of 24–72 h, that is not often compatible with the dairy industry, is still necessary to obtain results.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the qPCR assay identifies successfully all the submitted CNS isolates with high accuracy indicating that the reported low Se is probably due to the effect of the sampling technique. We reported the full description of 15 CNS species isolated from the teat skin samples in Mahmmod et al () including Staph. arlettae, Staph.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the qPCR assay identifies successfully all the submitted CNS isolates with high accuracy indicating that the reported low Se is probably due to the effect of the sampling technique. We reported the full description of 15 CNS species isolated from the teat skin samples in Mahmmod et al (2018b) Skjølstrup et al (2018) reported that Se of qPCR on teat skin was 30% for the identification of Staph. aureus compared with 91% for a sampling method where special qPCR swabs 'FLOQ swabs' were directly applied on the teat skin for swabbing.…”
Section: Estimates Of Qpcr and Bc For Tacmentioning
confidence: 99%